Islamic Hire- Purchase Ijarah Thumma Al-Bai' (AITAB) - Razli Ramli, Hasleenda Onn (Islamic Banking and Finance Institute Malaysia, 2007)
Buku ini Berisi Tentang Sewa-Beli-Islam Ijarah Thumma Al-Bai '(AITAB)